Development of novel yarns containing carboxymethyl cellulose and alginate fibers for wound dressing applications - (:unkn) unknown (Nova Science Publishers, Inc., 2015)
The main objective of this study is to design, fabricate and characterize novel yarn structures containing gelling materials for medical textile applications. The yarns were developed to produce textile based 3D wound dressings. Carboxymethyl cellulose and alginate fibers have been employed to produce the yarns. Prior to producing medical yarns, the main properties of CMC and alginate fibers were investigated in terms of their tensile, absorbency and swelling behaviors. The novel part of the study is related to the 100% CMC and 100% alginate yarns spinning trials and their limitations. A number of experiments were carried out in order to spin novel 100% CMC and 100% alginate yarns. The developed CMC and alginate yarns were compared with a common cotton yarn. The idea behind this comparison was to demonstrate the possible yarn performances during fabric forming. It has been clearly seen that it is possible to make yarns from CMC and alginate fibers and the produced yarns are comparable with the cotton yarn. © 2015 by Nova Science Publishers, Inc. All rights reserved.
Keywords: Alginate; Biomaterials; CMC fibers; Medical textiles; Wound dressing